Relationship between learning strategies and academic performance: a comparison between accreditation of prior experiential learning (APEL) and regular entry undergraduates - Saw Fen Tan; Arathai Din Eak; Li Hsien Ooi; Anna Christina Abdullah (AAOU Journal, 2021)
Purpose – The purpose of this study aims to compare the academic performance and types of learning strategies used by APEL and regular entry undergraduates. It also explored the relationship between the academic performance and the types of learning strategies utilised by these two groups of undergraduate. Design/methodology/approach – This quantitative study involved 400 undergraduates from an open distance learning (ODL) institution. A correlational research design was used in this study. Data were collected through archival data and questionnaire. Independent t-test and Pearson’s correlation analyses were performed using SPSS. Findings – Regular entrants were found to perform slightly better than APEL entrants. There is no significant difference between the types of learning strategies used by APEL and regular entrants. For both groups, the higher performers adopted time and study environment management as well as effort regulation strategies. Besides this, there was no correlation between cognitive skills and peer learning with their academic performance. Meta-cognitive self-regulation and help-seeking which were found to affect the regular entrants’ academic performance did not correlate with those of APEL entrants. Research limitations/implications – This study was conducted within only one institution. The generalisation of findings may therefore be limited. Future studies could be conducted to include students from several institutions. Practical implications – Time management training could be provided to students. Additional support, like foundation courses and supplementary readings, could be provided to APEL entrants to support their learning. Originality/value – The findings would be beneficial to ODL institutions who offer APEL entry to understand the academic performance and learning strategies used by APEL entrants relative to regular entrants.